2020
DOI: 10.3390/nano10040795
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Solar Light Photocatalytic Activity of Ag Doped TiO2–Ag3PO4 Composites

Abstract: Composites comprised of Ag3PO4 and bare TiO2 (TiO2@Ag3PO4) or silver doped TiO2 (Ag@TiO2–Ag3PO4) have been synthesized by coupling sol–gel and precipitation methods. For the sake of comparison, also the bare components have been similarly prepared. All the samples have been characterized by X-ray diffraction (XRD), UV-vis diffuse reflectance spectroscopy (DRS), scanning electron microscopy (SEM), Fourier transformed infrared spectroscopy (FTIR), photoelectrochemical measurements, and specific surface area (SSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 56 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…However, decreased crystal dimensions increases the microstructural strain that also shrinkages the crystallite size. [ 13 ] The decrement observed from 12.2 nm for bare TiO 2 to 8.4 nm of Ag‐TiO2/rGO composite as a similar phenomenon observed in literature reports as ionic radii of silver ion different than titanium ion. [ 14 ]…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…However, decreased crystal dimensions increases the microstructural strain that also shrinkages the crystallite size. [ 13 ] The decrement observed from 12.2 nm for bare TiO 2 to 8.4 nm of Ag‐TiO2/rGO composite as a similar phenomenon observed in literature reports as ionic radii of silver ion different than titanium ion. [ 14 ]…”
Section: Resultssupporting
confidence: 80%
“…So narrowed band gap makes these samples better candidate for optoelectronic and photocatalytic applications. [ 13,19,20 ]…”
Section: Resultsmentioning
confidence: 99%
“…The UV‐DRS spectra were transformed to Kubelka‐Munk function, 101 following which Tauc plot ([F(R). hν] n vs. hν (hν = photon energy, eV and n = 1/2)) was used for the determination of the indirect band gap values of all samples 102 (Figure 12).…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers reported that the presence of Ag in TiO 2 displayed a redshift toward the visible region. Indeed, they predicted that the addition of silver ions is often used to create transitional energy states resulting from the high electronic interaction between the orbitals of TiO 2 and silver [68].…”
Section: Uv Analysismentioning
confidence: 99%